Effect of Manganese Chloride in Histological of Ovaries in Albino mice (Baghdad Science Journal, 2011)
Manganese is considered as one of heavy metals with high toxicity .This element has been used widely in various industries and it is spread with huge quantities in polluted industries areas. As a result the concentrations of this element in the environment have increased and consequently producing acute toxic effects in different tissues and organs of all organisms. A study has been conducted on (30) female of Swiss albino mice, to find out the effect of manganese chloride in histopathological changes of ovaries. The study includes, giving the manganese chloride with concentrations (150, 200 and 250 mg/kg) for (15, 30 and 45 day) for each concentration. The study has reported the existence of histopathological changes in the ovaries including congestion, reddening with emergence of blood vessels. In addition to that there is decrease in their weights and their sizes get smaller. Also there is degeneration in cells of the corpus lutum, and decrease in number of these bodies in the ovaries, with increase in atretic follicles, especially within the concentration (250 mgkg) for (45 day).